Indeks Penulis dan Subjek Jurnal Veteriner 2023 - I Wayan Batan (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2023)
Indeks Penulis dan Subjek Jurnal Veteriner 2023